2018
DOI: 10.32502/sm.v9i1.121
|View full text |Cite
|
Sign up to set email alerts
|

Laporan Kasus: Kutil Kelamin pada Uretra dan Meatus Uretra yang Diterapi dengan Krim 5-Fluorourasil 5%

Abstract: Angka kejadian kutil kelamin (KK) di seluruh dunia terus meningkat. Sampai saat ini belum terdapat terapi yang lebih unggul dibanding dengan terapi lainnya. Krim 5-fluorourasil (5-FU) 5% merupakan salah satu terapi untuk KK pada meatus uretra dan uretra. Krim 5-FU 5% adalah antimetabolit pirimidin fluorinated yang memiliki fungsi sebagai agen antineoplastik dengan menghambat sintesis DNA. Seorang pasien laki-laki berusia 27 tahun dengan KK tipe kondiloma akuminta (KA) di  meatus uretra dan uretra. Pada meatus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…1 It is estimated that around 500,000 to 1,000,000 new CA cases are diagnosed annually. 2 The prevalence rate of CA in Indonesia estimated around 5-19%. This was supported by a study conducted at the Bali Sanglah Hospital in 2015-2017, and it reported a higher prevalence in males than females.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 It is estimated that around 500,000 to 1,000,000 new CA cases are diagnosed annually. 2 The prevalence rate of CA in Indonesia estimated around 5-19%. This was supported by a study conducted at the Bali Sanglah Hospital in 2015-2017, and it reported a higher prevalence in males than females.…”
Section: Introductionmentioning
confidence: 99%
“…6 The ideal therapy for CA should be simple, inexpensive, effective, and does not cause side effects. 2 Specific therapy is not yet available so that eradication is not maximal, causing a significant clinical problem and frequent recurrences. 2,7 The standard therapies for anal warts require medical professionals to apply, such as trichloroacetic acid, CO2 laser, cryotherapy, and cautery.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations